Aluminum-free glass ionomer cements containing 45S5 Bioglass(®) and its bioglass-ceramic - Zandi Karimi, Alireza (J Mater Sci Mater Med, 2021)
Although the incorporation of bioactive glasses into glass ionomer cements (GICs) has led to promising results, using a bioactive glass as the only solid component of GICs has never been investigated. In this study, we developed an Al-free GIC with standard compressive strength using various combinations of 45S5 Bioglass(®) and its glass-ceramic as the solid component. The glass-ceramic particles with 74% crystallinity were used for this purpose as they can best act as both remineralizing and reinforcing agents. Strengthening mechanisms including crack deflection and crack-tip shielding were activated for the GICs containing 50–50 wt% bioglass and bioglass-ceramic as the optimum ratio. The progression of the GIC setting reaction at its early stages was also monitored and verified. We also discussed that our bimodal particle size distribution containing both micron- and nanosized particles may enhance the packing density and integrity of the structure of the cements after setting. In such GICs produced in this study, the toxic effects of Al are avoided while chemical bonds are expected to form between the cement and the surrounding hard tissue(s) through interfacial biomineralization and adhesion. [Image: see text]